Islamic Law: KONTROVERSI DINAR DIRHAM SEBAGAI ALAT TUKAR JUAL BELI DALAM PERSPEKTIF FIQIH KONTEMPORER - Mustaqim, Dede Al; Abdul Fatakh (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2023)
The issue with this controversy is the use of dinar and dirham as the standard currency in the past, which is considered by some Muslim groups as a superior exchange tool for buying and selling compared to modern currency. However, on the other hand, the use of dinar and dirham is deemed impractical in its application. The purpose of this research is to explore the views of contemporary fiqh scholars on the use of dinar and dirham as a means of exchange in buying and selling, and to examine to what extent the use of dinar and dirham can be applied in the context of modern economics. The research method employed is literature study by collecting and analyzing various opinions of scholars and relevant literature. The results of the study show that contemporary fiqh scholars have diverse views on the use of dinar and dirham as a means of exchange in buying and selling. Some scholars argue that the use of dinar and dirham is still relevant in the context of modern economics because they have stable intrinsic value and can avoid inflation problems. However, there are also those who believe that the use of dinar and dirham is limited to the past and is not practical in its use in the modern era. The conclusion of this research is that the use of dinar and dirham as a means of exchange in buying and selling remains a topic of debate in the perspective of contemporary fiqh. The decision to use dinar and dirham or other currencies should be based on the convenience and needs of society, as well as adequate infrastructure support for their use. This research can provide a more comprehensive understanding of the controversy surrounding the use of dinar and dirham in the context of contemporary fiqh and can serve as a reference for academics and society to make wise decisions in the use of exchange tools for buying and selling.